Reconstruction of the Historical (1750–2020) Mass Balance of Bordu, Kara-Batkak and Sary-Tor Glaciers in the Inner Tien Shan, Kyrgyzstan - Van Tricht, Lander; Paice, Chloë Marie; Rybak, Oleg; Satylkanov, Rysbek; Popovnin, Victor; Solomina, Olga; Huybrechts, Philippe (Frontiers in Earth Science, 2021)
The mean specific mass balance of a glacier represents the direct link between a glacier and the local climate. Hence, it is intensively monitored throughout the world. In the Kyrgyz Tien Shan, glaciers are of crucial importance with regard to water supply for the surrounding areas. It is therefore essential to know how these glaciers behave due to climate change and how they will evolve in the future. In the Soviet era, multiple glaciological monitoring programs were initiated but these were abandoned in the nineties. Recently, they have been re-established on several glaciers. In this study, a reconstruction of the mean specific mass balance of Bordu, Kara-Batkak and Sary-Tor glaciers is obtained using a surface energy mass balance model. The model is driven by temperature and precipitation data acquired by combining multiple datasets from meteorological stations in the vicinity of the glaciers and tree rings in the Kyrgyz Tien Shan between 1750 and 2020. Multi-annual mass balance measurements integrated over elevation bands of 100 m between 2013 and 2020 are used for calibration. A comparison with WGMS data for the second half of the 20th century is performed for Kara-Batkak glacier. The cumulative mass balances are also compared with geodetic mass balances reconstructed for different time periods. Generally, we find a close agreement, indicating a high confidence in the created mass balance series. The last 20 years show a negative mean specific mass balance except for 2008-2009 when a slightly positive mass balance was found. This indicates that the glaciers are currently in imbalance with the present climatic conditions in the area. For the reconstruction back to 1750, this study specifically highlights that it is essential to adapt the glacier geometry since the end of the Little Ice Age in order to not over- or underestimate the mean specific mass balance. The datasets created can be used to get a better insight into how climate change affects glaciers in the Inner Tien Shan and to model the future evolution of these glaciers as well as other glaciers in the region.